Globalização e cafés especiais: a produção do comércio justo da Associação dos Agricultores Familiares do Córrego D’Antas - ASSODANTAS, Poços de Caldas (MG) / Globalization and specialty coffees: the Fair trade production of Associação dos Agricultores Familiares do Córrego D’Antas - ASSODANTAS, Poços de Caldas (MG) - Samuel Frederico; Marcela Barone (Sociedade & Natureza)
Since the last major international coffee crisis, in the 1990s, the production of specialty coffee has been considered one of the main market alternatives for small farmers. However, the increase in world consumption of this type of coffee has also attracted the attention of major exporters, roasters and retailers, with consequent standardization of production. On the one hand, the entry in such markets has important benefits for small producers, particularly in countries recognized by the production of lower quality coffee and insufficient collective organization of farmers, as the Brazilian case, on the other hand, external regulation and the role of large companies have extended the differences of power and distribution of value along the productive spacial circuit. Therefore, this article aim to examine the paradox resulting from the insertion of small producers of the Associação dos Agricultores familiares do Córrego D’Antas, Poços de Caldas (MG), in the Fairtrade market. For this, starts the debate on globalization and standardization of specialty coffee production. Then deepens the analysis in Fairtrade and finally, it highlight the benefits and challenges faced by Assodantas.